Brexit and the UK's public finances - Carl Emmerson; Paul Johnson; Ian Mitchell; David Phillips (Institute for Fiscal Studies (IFS), 2016)
If the result of the referendum on 23 June leads to the UK leaving the EU, there will be impacts on the UK public finances. This report aims to set out the possible impacts, focusing particularly on the short run, given that the Chancellor wishes to achieve a budget balance by the end of this parliament. We also look at possible long-run consequences. The overall impact on the public finances will depend on two distinct components, each of which is uncertain to some degree: - The mechanical effect. As a net contributor to the EU, leaving the EU would strengthen the public finances because our net contribution would fall. But given uncertainty over the form of any subsequent arrangement with the EU, it might not necessarily fall to zero. - The national income effect. Any effect of leaving the EU on UK national income would affect the public finances. A rise in national income would strengthen the public finances, a fall would weaken them ...
Keywords: 330